Immature Terminal Deoxynucleotidyl Transferase Positive B Cells are Detected in a Subset of Adult and Pediatric Liver Biopsies. Issue 4 (April 2019) - Wen, Kwun Wah; Gill, Ryan M.
Abstract : Terminal deoxynucleotidyl transferase (TdT) is a nuclear enzyme restricted to precursor lymphoid cells and their malignant counterparts; immunohistochemical TdT labeling is helpful in recognition of lymphoblasts, which can resemble mature lymphocytes. The diagnosis of B-lymphoblastic leukemia/lymphoma (B-ALL) is occasionally first encountered on liver core biopsy, but TdT immunostain specificity for B-ALL is not clearly established in this setting, which can be problematic when only a few TdT-positive cells are identified. In this study, we evaluated the incidence and distribution of immature B lymphocytes coexpressing TdT and PAX-5, in pediatric and adult liver biopsies, to determine whether a normal complement of hepatic immature B cells can be detected, which must be recognized in a workup to exclude B-ALL. We selected 41 pediatric and adult liver biopsies with a significant portal and/or sinusoidal hematolymphoid infiltrate and performed immunohistochemical stains for TdT and PAX-5 to identify and categorize distribution of immature B cells. TdT-positive cells were detected in 40% of pediatric liver biopsies with a significant hematolymphoid infiltrate (4/10), which included all biopsies from neonates (and infants under 9 wk of age). In adults, immature B-cell infiltrates were less common (6%, 2/31). Dual immunostaining was performed on 2 cases of neonatal hepatitis, which documented B-cell lineage in at least a subset of TdT-positive cells and there was no colabeling with CD3. Immature B cells can be detected in liver biopsies in a variety of clinical settings, most commonly in children, and presence of a few TdT-positive cells cannot be considered entirely specific for involvement by B-ALL. Further workup for B-ALL can be warranted if there is more extensive multifocal portal and/or sinusoidal involvement by blasts with TdT labeling.